2021
DOI: 10.1080/12298093.2020.1857009
|View full text |Cite
|
Sign up to set email alerts
|

First Report: Diversity of Endophytic fungi Possessing Antifungal Activity Isolated from Native Kougoed (Sceletium tortuosum L.)

Abstract: Forty-three ( n = 43) endophytic fungi with different morphologic characteristics were from a medicinal plant Sceletium tortuosum, were utilized to investigate their antifungal effectiveness against pathogenic fungi. All fungal isolates exhibited antifungal activity against one or more pathogens in the dual culture test whereas only 33 fungal culture filtrates (77%) showed decent antifungal effect. Fusaria and Aspergillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In light of the ongoing research on alkaloids isolated from Sceletium plants, several studies have reported the biological and pharmacological potentials of Sceletium plants [ 1 , 30 , 31 ]. Traditional preparation of the plants through fermentation, referred to as “kougoed”, has renewed attention since it was reported that the fermented form produces higher levels of alkaloids than the dried the plant material [ 32 ].…”
Section: Biological and Pharmaceutical Properties Of Sceletium Spmentioning
confidence: 99%
“…In light of the ongoing research on alkaloids isolated from Sceletium plants, several studies have reported the biological and pharmacological potentials of Sceletium plants [ 1 , 30 , 31 ]. Traditional preparation of the plants through fermentation, referred to as “kougoed”, has renewed attention since it was reported that the fermented form produces higher levels of alkaloids than the dried the plant material [ 32 ].…”
Section: Biological and Pharmaceutical Properties Of Sceletium Spmentioning
confidence: 99%